Exchange between populations of Adamussium colbecki (Mollusca : Bivalvia) in the Ross Sea - GUIDETTI M; CHIANTORE M; ALBERTELLI G; CATTANEO VIETTI R.; MARCATO, STEFANIA; PATARNELLO, TOMASO (Antarctic Science, 2006)
The endemic Antarctic scallop Adamussium colbecki (Mollusca: Bivalvia) represents a key species in the Ross Sea littoral benthic ecosystem, locally reaching very high densities. This species has an annual gametogenic cycle, with a summer spawning event, and a pelagic larval behaviour. This paper aims at describing population structure and genetic polymorphism (using AFLP) of the large populations inhabiting the Ross Sea (Terra Nova Bay and McMurdo Sound) in order to investigate possible genetic exchange between A. colbecki in these areas. In Terra Nova Bay, size-frequency distributions show, generally, the dominance of large individuals, although site related differences are found in the abundance of smaller size classes (less than 40 mm), suggesting that recruitment is not a regular event. All McMurdo sites are characterized by large individuals and, at least during this sampling period, recruitment is completely absent. Nuclear DNA analyses show that the largest differences are found at the largest scale (between McMurdo Sound and Terra Nova Bay), but all populations sampled, even at a smaller spatial scale, have a well-settled genetic structure, notwithstanding the pelagic larval strategy. The panmixia hypothesis has therefore to be rejected for this species